2013
DOI: 10.1111/ijac.12172
|View full text |Cite
|
Sign up to set email alerts
|

Sinterability of Forsterite Prepared via Solid‐State Reaction

Abstract: In this work, the sinterability of forsterite powder synthesized via solid‐state reaction was investigated. X‐ray diffraction (XRD) analyses indicate that the synthesized powder possessed peaks that correspond to stoichiometric forsterite. Scanning electron micrographs revealed that the powders were formed agglomerates, which were made up of loosely packed fine particles. Subsequently, the forsterite powders were cold isostatically pressed into a disk shape under 200 MPa and sintered in air at temperature rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Thus, the sinterability is higher for the powders calcined at lower temperatures. For the powders calcined at 700°C, the relative density of the corresponding ceramics is as high as 98.9% which is much higher than that for the ceramics prepared from powders made by the conventional solid‐state reaction process …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Thus, the sinterability is higher for the powders calcined at lower temperatures. For the powders calcined at 700°C, the relative density of the corresponding ceramics is as high as 98.9% which is much higher than that for the ceramics prepared from powders made by the conventional solid‐state reaction process …”
Section: Resultsmentioning
confidence: 84%
“…Figure (b) shows the XRD patterns of powders prepared at various temperatures by keeping the initial MgO/SiO 2 molar ratio at 2:1.3. It can be seen that single‐phase forsterite powders can be synthesized at 700°C, which is at least 400°C lower than the synthesis temperature required in conventional solid‐state reaction . During the MSS process, when the temperature exceeds the eutectic point of NaCl–KCl salt mixture, a liquid phase forms, which provides a liquid medium for the reaction of MgO and SiO 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8) It was found that the enstatite and MgO interphases are very stable in forsterite ceramic even though a sufficient solid-state reaction between magnesium oxide (MgO) and talc [Mg 3 Si 4 (OH) 2 ] occurs in a temperature range of 12001500°C for 2 h. 9) A high-strength forsterite ceramic can be prepared using magnesium oxide (MgO, 97 wt %) and talc [Mg 3 Si 4 O 10 (OH) 2 , 99 wt %] when sintered at 12001500°C, a maximum density of 91% and the highest mechanical properties were obtained respectively when sintered at 1500 and 1400°C. 10) A forsterite was prepared utilizing 57.62 wt % serpentine and 42.38 wt % magnesium chloride water solution when sintered at 1300°C for 2 h, a small amount of SiO 2 , MgSiO 3 and MgO still companied.…”
Section: Introductionmentioning
confidence: 99%